Model Pendampingan Activity-Based Costing Digital untuk Penguatan Manajemen Biaya Produk Pertanian Lokal Kalimantan Barat - Pratiwi Kurniati; Syahbudi Syahbudi; Dwi Surya Atmaja; Verdianti Verdianti; Fitri Jayanti; Dini Lestary; Monica Olivia; Fitri Giani; Novi Nurmayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2026)
This community service activity aimed to strengthen the capacity of 20 farmer group participants under CV. Duta Alam in Ketapang Regency, West Kalimantan, in managing production costs for local agricultural products. The main problem faced by the partners was the limited ability to record, classify, and calculate production costs accurately. Most farmers still relied on manual records and market prices when determining selling prices. The success indicators of this program were measured by a participant attendance rate of 80% and a quantifiable improvement in digital literacy and cost management skills. The results showed that initially, 65% of participants recorded farming costs regularly, but 75% used handwritten records, and 75% had never heard of Activity-Based Costing. After the mentoring activity, all 20 participants successfully met the competency standards, demonstrating the ability to identify production activities, classify overhead costs, and utilize spreadsheets to compare traditional costing with Activity-Based Costing for durian, jengkol, petai, and matoa seedlings. The activity concluded that digital-based Activity-Based Costing effectively overcomes the farmers' technological constraints and supports more accurate cost calculation. Theoretically, this activity demonstrates that the Activity-Based Costing (ABC) method can be adaptively applied to small-scale agriculture through simplified digital tools. Practically, this mentoring significantly enhances the farmers' economic independence by ensuring precise product pricing, minimizing potential financial losses, and accelerating the digital transformation of traditional farmer groups in cost management.